PHYSICOCHEMICAL PROPERTIES OF ACHA-PEANUT COMPOSITE FLOUR ENRICHED WITH CARROT AND ORANGE-FLESHED SWEET POTATO - Sule, Stephen (Food and Feed Research, 2024)
Physicochemical characteristics of acha-peanut composite flour separately enriched with carrot and orange-fleshed sweet potato(OFSP) flours, yielding four samples based on a 19g protein target were assessed: A (100% acha), AP (81.08% acha + 18.92% peanut), APC (64.21% acha + 20.64% peanut + 15.15% carrot), and APO (64.55% acha + 20.74% peanut + 14.71% OFSP). Sample APO had significantly (p
Keywords: Fonio; viscosity; minerals; vitamins; nutrient enrichment; antinutrients